(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
درس تأثير الملوحة في إنبات البذور ونمو الجذور والسويقات لصنفين من عباد الشمس 70-S-441) و70-S-443) تحت شروط مخبرية . تمّ استخدام 6 تراكيز مختلفة من NaCl (5،10, 12,5، 15، 17,5 و20 غ/لتر). تمّ إنبات البذور في أطباق بتري تحوي الوسط المدروس والتي حضنت بدرجة حرارة 25 م˚. بينت النتائج تناقص النسبة المئوية للإنبات وأطوال الجذور والسويقات مع زيادة تراكيز NaCl. أظهرت بذور الصنف 70-S-441 نسبة إنبات أعلى وزيادة في أطوال الجذور والسويقات مقارنة ببذور 70-S-443. لوحظ وجود فروق معنوية بين الشاهد والبذور المعاملة بعد 6 أيام من الزراعة. نتج تثبيط إنبات البذور بالتركيز 17.5 غ/لتر بالنسبة للصنف 70-S-443، وبالتركيز 20 غ/لتر بالنسبة للصنف 70-S-441. The effect of salinity on seeds germination, root and hypocotyls growth of two cultivars of Sunflower (70-S-441 and 70-S-443 was studied under laboratory conditions. Six different NaCl concentrations (5, 10, 12.5, 15, 17.5, 20 g/liter) were used. Seeds were germinated in Petri dishes with test solution qui placed in an incubator at 25˚ C. The results showed that germination percentage, root and hypocotyl lengths decreased with increasing concentration of NaCl.The seeds of the cultivar 70-S-441 exhibited higher germination percentage, increasing of root and hypocotyl lengths compared to the 70-S-443 cultivar seeds. After six days of incubation, significant differences were observed between control and treated seeds. Seeds germination was inhibited by 17.5 g/l for the cultivar 70-S-443 and by 20 g/l for 70-S-441.